EFEKTIVITAS ALAT PENUKAR KALOR ALIRAN BOLAK BALIK DENGAN FLUIDA PANAS CAIR DAN GAS - Indra Hermawan (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2019)
The heat exchangers is an equipment used to change the temperature and phase of a type of fluid. The process occurs by utilizing the process of heat transfer from high temperature fluids to low temperature fluids. The shell and tube heat exchanger consists of a bundle of pipes connected in parallel and placed in a pipe (shell). One fluid flows in a pipe bundle, while the other fluid flows outside the pipe in the same direction, opposite, or crossing. To improve the efficiency of heat exchange, shell and tube heat exchanger are usually installed with baffles. The purpose of this study is to determine the effectiveness of the heat exchanger by using the LMTD (Log Mean Temperature Deferences) method. The results of the study are the highest LMTD values located in experiment 6 with a value of 6.75oC and the lowest in experiment 1 is 3.31oC. By using the LMTD method it was found that the greatest effectiveness value was in the first experiment of 0.9773 (97.73%), while the smallest effectiveness value was in experiment 10 with a value of 0.87069 (87.07%).